Holy treasure and sacred song : relic cults and their liturgies in medieval Tuscany - Brand, Benjamin David, 1977- (Oxford University Press, 2014)
This title explores the complex interplay between relic cults and the liturgy in medieval Tuscany. Drawing on documentary, literary and visual evidence rarely considered together, it reveals that liturgical texts, music, and ritual were integral to the clergy's well-informed promotion of saints buried in their churches.